(untitled) (Research, Society and Development, 2019)
When reflecting on the teaching of Mathematics, for a long time we thought of the formulas and concepts. Given the abstract character and the mechanical form with which it was applied to the students in times past, it distanced them of the practice. Currently, students present a fragility in the learning of contextualized mathematics to concrete situations related to the real world, because there is still a teaching that prioritizes mechanization and memorization. The present work aims to analyze educational contextualization relating to the teaching of mathematics. Another objective found in our work is to research on the participation of play activities in the learning process of aggregated mathematics, environmental education, approaching concrete from the abstract, collaborating in the creation of new didactic resources that link the interdisciplinarity and mathematical thinking present in the Law of Guidelines and Bases of Education 9394/96. At first, analyzes were made of mathematical games constructed with recyclable materials linked to the Numeric and Algebraic axis; Geometry axis; of Measures and Greatness. Subsequently, mathematical games linked to flat geometry were proposed that were applied to the students of the initial grades of elementary school. The study pointed out that students were able to identify and recognize geometric figures, develop and identify logical and conceptual abilities, increasing curiosity, creativity, self-confidence and the perception of geometry as a challenge that they can overcome. It was concluded that in the course of the games that the errors stimulated the students to new attempts, with planning of better plays from the knowledge previously acquired.